Hepato‐pancreato‐biliary and transplant surgery experience among New Zealand general surgery trainees. Issue 6 (7th March 2021) - Rowcroft, Alistair; Joh, Daniel; Pandanaboyana, Sanjay; Loveday, Benjamin
Abstract: Background: Subspecialty surgery experience during general surgery training in Australasia is influenced by many factors, including duration of training, training location and the introduction of post‐fellowship training programmes. Experience in hepato‐pancreato‐biliary (HPB) and transplant surgery is part of the general surgery curriculum, although trainee experience in these subspecialties has not been quantified in this region, which is relevant to post‐fellowship training programmes. Therefore, the aim of this study was to quantify the HPB and transplant operative experience of New Zealand (NZ) general surgery trainees. Methods: Operative logbook data were analysed for all NZ trainees from 2013 to 2017, including procedures categorized as pancreatic, biliary, hepatic and transplant surgery only. The number of cases within each category was used to model the cumulative operative experience over a 5‐year training programme. Results: During the study period, 118 trainees (303 trainee years) recorded 15 662 HPB and transplant procedures. Of these, 13 838 (88.4%) were cholecystectomies (mean cumulative experience 219.3 cases). Excluding cholecystectomy, trainees had a mean cumulative experience of 5.7 biliary, 7.5 pancreatic, 8.1 liver and 4.2 transplant procedures during their training. Transplant experience was predominantly access for peritoneal dialysis (228/260, 86.7%), with cumulative transplant experience otherwise reaching 0.47 procedures over 5 years. Conclusion: Exposure to HPB and transplant surgery during general surgery training in NZ is limited beyond cholecystectomy. Additional exposure during post‐fellowship training is likely required for general surgeons to practice in these subspecialties. Abstract : This is a retrospective review of logbook data for NZ trainees from 2013 to 2017. Overall, 118 trainees recorded 15 662 procedures, of which 88% were cholecystectomies. Exposure to other hepato‐pancreatico‐biliary and transplant surgeries was limited.